A step a day... / Suzana Ab. Rahim - Ab. Rahim, Suzana (Academy of Language Studies, 2022)
Have you ever tried hopscotching? Or been in a 3-legged race? How did you feel? Was it an experience you would rather not repeat? Well, that is just me ... in a constant competition against no one but me. An amputee who we can only imagine or usually see on the silver screen, often portrayed as a villain - either with a hook as in the pirates or captain hook, or the AI in the 'manners maketh men' movie ... and I digress ... It is rather overwhelming to state in words those emotions that had swept over me but I shall try. This short jotting is just a sharing of what my early experience has been as a 'minus one'.